Steel for high-steel-grade anti-SSC oil well pipe, production method of steel, produced oil well pipe, heat treatment process and application

By optimizing the alloy composition and heat treatment process, high-steel grade SSC-resistant oil well pipe steel was developed, which solved the problem of difficult to take into account both high-strength and hydrogen sulfide corrosion resistance in the existing technology, and achieved excellent performance of oil well pipes in high-corrosion environments, and was suitable for deep well oil and gas mining.

CN119710487AActive Publication Date: 2025-03-28МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510035585.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-28
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The prior art is difficult to develop 135ksi steel grade oil well pipes that meet high strength and hydrogen sulfide corrosion requirements in highly corrosive deep wells.

Method used

By optimizing the alloy composition and heat treatment process, a high-steel grade SSC-resistant oil well pipe steel is designed, including Cr, Ni, Mo, Ti, B, Al, V, RE and other elements. The oil well pipe is produced by arc furnace smelting, LF furnace refining, RH vacuum degassing and continuous casting processes, and the strength and toughness of the material and corrosion resistance of hydrogen sulfide are improved through the heat treatment process of two quenching and secondary tempering.

Benefits of technology

It achieves high strength and excellent corrosion resistance of the oil well tube at room temperature. It can pass the hydrogen sulfide corrosion resistance test of NACE TM0177 standard A method without fracture for 720 hours. It is suitable for oil well mining in 10,000 meters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710487A_ABST
    Figure CN119710487A_ABST
Patent Text Reader

Abstract

The invention provides steel for a high-steel-grade anti-SSC oil well pipe, a production method of the steel, the produced oil well pipe, a heat treatment process and application of the steel. The steel comprises the following components: 0.95%-1.20% of Cr, 0.40%-0.60% of Ni, 0.75%-0.95% of Mo, 0.030%-0.050% of Ti, 0.0010%-0.0030% of B, 0.020%-0.045% of Al, 0.10%-0.20% of V, 0.0010%-0.0020% of RE, 0.25%-0.30% of C, 0.15%-0.30% of Si, 0.60%-0.75% of Mn, less than or equal to 0.010% of P, less than or equal to 0.0015% of S and the balance of Fe and other inevitable impurities. Through component design, production method and heat treatment process optimization, the obtained oil well pipe has good obdurability and excellent hydrogen sulfide corrosion resistance, and can be used for myriameter oil well exploitation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alloy steel, and in particular relates to a high-grade SSC-resistant steel for oil well pipes, a production method thereof, the produced oil well pipes, a heat treatment process and applications thereof. Background Art

[0002] With the continuous exploitation of oil and gas over the past few decades or even a century, shallow oil and gas resources have been exploited and exhausted ahead of schedule. The exploration and development of oil and gas in deep wells containing highly corrosive hydrogen sulfide (H2S) gas requires that the material has excellent corrosion resistance while ensuring high strength. The 125ksi grade (yield strength of at least 862MPa) steel on the market currently cannot meet the requirements of working in highly corrosive deep wells, and higher steel grade SCC resistant oil well pipe products are urgently needed.

[0003] Currently, many studies are trying to develop 135ksi steel grade sulfur-resistant oil well pipes. However, it is difficult for the developed 135ksi steel grade sulfur-resistant oil well pipes to meet the index requirements while being resistant to H2S corrosion, especially it is difficult to pass the assessment of NACE TM0177 standard A solution.

[0004] The Chinese patent with publication number CN110616366A published on December 27, 2019, discloses a 125ksi steel-grade sulfur-resistant oil well pipe and its manufacturing method, whose composition is: C: 0.20-0.30%, Si: 0.1-0.5%, Mn: 0.2-0.6%, Cr: 0.30-0.70%, Mo: 0.60-1.00%, V: 0.10-0.20%, Nb: 0.01-0.06%, Ti: 0.015-0.035%, W: 0.20-0.60%, Al≤0.1%, N≤0.008%, and the balance is Fe and other inevitable impurities. The Cr-Mo-W system is used to obtain the 125ksi steel-grade sulfur-resistant oil well pipe, and its low-temperature toughness is not disclosed.

[0005] The Chinese patent with publication number CN103160752A published on June 19, 2013 discloses a high-strength seamless steel pipe with excellent low-temperature toughness and a manufacturing method thereof, wherein the composition is: C: 0.15% to 0.20%, Si: 0.20% to 0.30%, Mn: 0.20% to 0.50%, P: ≤0.010%, S: ≤0.003%, Cr: 0.6% to 0.8%, Mo: 0.4% to 0.7%, Ni: 1.0% to 1.4%, Nb: 0.01% to 0.035%, Als: 0.01% to 0.05%, and the Cr-Mo-Ni system is used to obtain 125ksi steel grade oil well pipe. Although the toughness is greatly improved,

[0006] The impact energy at -60℃ reaches over 40J, but the anti-sulfur performance is not guaranteed.

[0007] Therefore, it is very necessary to provide a steel for oil well pipes that has strength and toughness that meet the index requirements while taking into account H2S corrosion resistance. Summary of the invention

[0008] The object of the present invention is to provide a high-grade SSC-resistant oil well pipe steel and a production method thereof, and to obtain a 135ksi steel grade high-strength SSC-resistant oil well pipe steel that can be continuously cast into a small diameter round billet and is suitable for electric furnace production through component design.

[0009] Another object of the present invention is to provide an oil well pipe and a heat treatment process thereof. The oil well pipe produced by the above-mentioned high-grade SSC-resistant oil well pipe steel is subjected to a designed heat treatment process to obtain a tempered troostite matrix at room temperature with a dispersed and refined second phase, a lower dislocation density and a high-angle grain boundary ratio, while improving the morphology of type II MnS and reducing the aggregation concentration of H atoms, so that the material has good strength and toughness and excellent resistance to hydrogen sulfide corrosion.

[0010] The last object of the present invention is to provide an application of an oil well pipe that can be used for exploitation in 10,000-meter oil wells.

[0011] The specific technical solutions of the present invention are as follows:

[0012] A high-grade SSC-resistant oil well pipe steel comprising the following components in percentage by mass:

[0013] Cr: 0.95~1.20%, Ni: 0.40~0.60%, Mo: 0.75~0.95%, Ti: 0.030~0.050%, B: 0.0010~0.0030%, Al: 0.020~0.045%, V: 0.10~0.20%, RE: 0.0010~0.0020%, C: 0.25~0.30%, Si: 0.15~0.30%, Mn: 0.60~0.75%, P≤0.010%, S≤0.0015%, and the rest are Fe and other inevitable impurities.

[0014] In the composition of the high-grade SSC-resistant oil well pipe steel, RE is at least one of the rare earth elements La and Ce.

[0015] The composition of the high-grade SSC-resistant oil well pipe steel also satisfies: T.O+[N]≤120ppm; and the five harmful elements Sn, Sb, As, Pb, and Bi are controlled at ≤0.010%;

[0016] The composition of the high-grade SSC-resistant oil well pipe steel also satisfies: α = -2.0×%Si+1.0

[0017] ×%Mn+1.3×%Mo+2.5×%Ni+2.0×%V+5.0%×(Ti+B)≥2.90%. Each element represents its mass percentage content in steel.

[0018] The composition of the high-grade SSC-resistant oil well pipe steel also satisfies: β = -5×(%Si+%Mn)+12

[0019] ×%Mo+10×%Cr+22×(%Ti+%B)+18×%V≥18.00%. Each element represents its mass percentage content in steel.

[0020] A production method for high-grade SSC-resistant oil well pipe steel includes the following process flow: electric arc furnace smelting→LF furnace refining→RH vacuum degassing→continuous casting.

[0021] The electric arc furnace smelting: steel is deoxidized and alloyed, and the amount of slag is strictly controlled.

[0022] The LF furnace refining: elements such as C, Si, Mn, Cr, Ni, Mo, V, Ti, and B are adjusted to target values, the white slag retention time is ≥20 minutes, and the smelting cycle is ≤80 minutes.

[0023] The RH vacuum degassing: pure degassing time ≥ 25min, soft blowing time ≥ 20min, [H] ≤ 1.0ppm after vacuum treatment, adding any one or more of rare earth elements La or Ce to make the rare earth content 0.0010-0.0020%.

[0025] The continuous casting: the superheat of the tundish is controlled to be 30-70°C above the liquidus line, and an immersion nozzle is used for pouring with protective slag to prevent secondary oxidation and absorb floating inclusions in the molten steel;

[0026] Continuous casting billet: The drawing speed of 380×450mm continuous casting billet should meet the requirements of 0.40~0.45m / min;

[0027] Continuous casting round billet: The diameter D of the continuous casting round billet and the casting speed v should meet v = 1.83 × (D / 1000) 2 -3.04×

[0028] (D / 1000)+1.41, where the unit of the continuous casting billet diameter D is mm, and the pulling speed is m / min; the crystallizer electromagnetic stirring frequency f1 and the continuous casting billet diameter D should meet the requirement of D / f1=200; the terminal electromagnetic stirring frequency f2 and the continuous casting billet diameter D should meet the requirement of D / f2=100, where the unit of the crystallizer electromagnetic stirring frequency f1 is Hz, the terminal electromagnetic stirring frequency f2 is Hz, and the unit of the continuous casting billet diameter D is mm. When calculating, simply substitute the value before the unit into the formula. If the pulling speed does not match the diameter, the low-multiple quality of the continuous casting billet may be poor, thereby affecting the subsequent overall performance of the material. The continuous casting billet diameter specifications of the present invention can be selected as follows: 380mm, 450mm, 500mm, 600mm, 700mm.

[0029] The present invention produces continuous casting to obtain 380×450 mm continuous casting square billets or continuous casting round billets with diameters D of 380 mm, 450 mm, 500 mm, 600 mm and 700 mm.

[0030] The present invention provides a heat treatment process for oil well pipes, which uses the oil well pipes produced by the above-mentioned high-grade SSC-resistant oil well pipe steel to perform heat treatment. The heat treatment includes two quenching and two tempering. Specifically, first quenching is performed, then tempering is performed; then secondary quenching is performed, and finally secondary tempering is performed.

[0031] The primary quenching: heating temperature W1 = AC3 + 30 ~ 50 ° C, holding time t1 is determined by the steel pipe wall thickness S, t = 3.5 × S, water cooling. Among them, the unit of heating temperature W1 is ° C, the unit of holding time t1 is min, and the unit of steel pipe wall thickness S is mm.

[0032] Primary tempering: tempering temperature 700-730℃, holding time t2 is determined by the steel pipe wall thickness S, t2=6×S, air cooling. The unit of holding time t2 is min, and the unit of steel pipe wall thickness S is mm.

[0033] Secondary quenching: heating temperature W2 = W1-20°C, holding time t3 is determined by the steel pipe wall thickness S, t = 3.5 × S, water cooling. Among them, the unit of heating temperature W2 is ℃, the unit of holding time t3 is min, and the unit of steel pipe wall thickness S is mm.

[0034] Secondary tempering: tempering temperature 680 ~ 710 ℃, holding time t4 is determined by the steel pipe wall thickness S, t4 = 6 × S, air cooling. Among them, the unit of holding time t4 is min, and the unit of steel pipe wall thickness S is mm.

[0035] The design of the two-time quenching and tempering process mainly reflects three aspects: First, the quenching process during the first quenching and tempering enables the workpiece to obtain martensite structure, and the martensite decomposes after tempering. During the heating and cooling process of the second quenching and tempering, the grains are further refined. The refined grains increase the grain boundary area, making it more difficult for hydrogen atoms to diffuse at the grain boundary, thereby improving the material's ability to resist hydrogen sulfide corrosion. Second, the two-time quenching and tempering can redistribute the alloying elements between the matrix and the carbide to form a more stable carbide phase, such as carbides of alloying elements such as Cr, Mo, V, and Ti. These carbides are dispersed at the grain boundary or phase boundary, playing the role of pinning dislocations, and also improving the corrosion resistance of the material. Third, the two-time quenching and tempering helps to make the stress distribution inside the workpiece more uniform and reduce stress concentration. This is especially important for workpieces that are subjected to complex stress in a hydrogen sulfide environment. Uniform stress distribution can reduce the risk of corrosion caused by excessive local stress. The temperature setting is selected according to the AC3 temperature, the purpose is to ensure that the material is completely austenitized, and the holding time is selected according to the wall thickness of the material.

[0036] The purpose of lowering the temperature of the secondary quenching in the present invention compared to the primary quenching is to further adjust the structure to make it more stable and uniform on the basis of retaining the effect of the primary quenching and refining the grains. At the same time, the lower secondary quenching temperature can reduce the generation of thermal stress and organizational stress, and improve the corrosion resistance of the material. The reason for lowering the secondary tempering temperature is to ensure the mechanical properties of the material, and the primary tempering temperature is higher to reduce the stress inside the material and improve the sulfur resistance of the material.

[0037] Furthermore, the production process of the oil well pipe includes the above-mentioned heat treatment, and the specific process is: continuous casting round billet → heating → pipe threading → sizing → heat treatment → steel pipe grinding → steel pipe flaw detection → fine machining → flaw detection → packaging and warehousing, and oil well pipes can be directly produced by continuous casting round billets with small diameters.

[0038] The oil well pipe provided by the present invention is produced by the above-mentioned heat treatment process. The room temperature mechanical properties of the oil well pipe are yield strength ≥950MPa, tensile strength ≥1050MPa, -20°C impact energy ≥100J, and elongation ≥16%. The oil well pipe passes the hydrogen sulfide corrosion resistance test using the American standard NACE TM0177 standard A method at a loading strength of 75% SMYS, a H2S partial pressure of 0.1MPa, and a temperature of 25°C, and no fracture occurs during the test for 720 hours.

[0039] The grain size at the half wall thickness of the end cross section of the oil well pipe is ≥8.5 level; the structure is: the area ratio of tempered bainite exceeds 98%.

[0040] The oil well pipe has a high-angle grain boundary ratio of ≤70% and a dislocation density of 7.0×10 13 / m 2 ~9.0×1013 / m 2 .

[0041] The total amount of Class A, Class B, Class C, Class D and Class DS inclusions of the oil well pipe is less than Level 4.0, and the Class A, Class B, Class C, Class D and Class DS inclusions do not exceed Level 1.0.

[0042] The application of the oil well pipe provided by the present invention can be used for exploitation of oil wells with a length of 10,000 meters.

[0043] The design ideas of the present invention are as follows:

[0044] C: Ensures the strength of steel, improves hardenability and thus increases the percentage of martensite transformation; in addition, increasing the C content can increase the number of carbides precipitated during tempering, and these carbides are good H traps: but too high a C content will not only cause segregation itself, but will also greatly increase the segregation of Mn and P, thereby reducing the SSC resistance, so the C content is controlled at 0.25-0.30%.

[0045] Mn: improves the strength and permeability of steel, but Mn is an easily segregated element. Excessive Mn content is easily segregated with S and P at the grain boundaries, so it is not good for the anti-SSC performance. The Cr and Mo contents designed in the present invention are relatively high, which are sufficient to ensure the hardenability and strength of the steel, so the Mn content is controlled at 0.60-0.75%.

[0046] Ni: Ni is an austenite stabilizing element, which has the function of expanding the phase region, increasing the stability of supercooled austenite, and improving the hardenability of steel. Ni is the main element for improving low-temperature toughness. By reducing the stacking fault energy of crystals in steel, it makes it easier for dislocations to slip under low temperature conditions, thereby preventing stress concentration under low temperature conditions and achieving excellent low-temperature toughness. However, too high Ni content will deteriorate the steel's anti-SSC performance. Therefore, the Ni content is controlled at 0.40-0.60%.

[0047] Cr: Improves strength and hardenability, improves corrosion resistance, but excessive Cr content will precipitate large Cr at the grain boundary during tempering 23 C6 carbide is not conducive to the resistance to H2S stress corrosion, so the Cr content is controlled at 0.95-1.20%.

[0048] Mo: It is an important solid solution strengthening and tempering precipitation strengthening element, and it improves the hardenability of steel. Mo carbides precipitate during high temperature tempering to improve tempering resistance, so sufficient Mo must be added to ensure high strength and high tempering temperature. In addition, Mo can also reduce the segregation of P at the grain boundary by reducing the diffusion coefficient of P, but when Mo is too high, coarse M2C and M6C carbides will be formed, which is not conducive to the resistance to H2S stress corrosion, so the Mo content is controlled at 0.75-0.95%.

[0049] V: Its role in quenched and tempered steel is to inhibit tempering softening and increase tempering temperature. During high temperature tempering, VC carbides are precipitated to play a precipitation strengthening role, thus ensuring that the dislocation density of the steel is reduced during high temperature tempering, improving the SSC resistance, and ensuring the high strength requirement of 135ksi; however, when the V content in the steel exceeds a certain upper limit, the SSC resistance will no longer be improved, so the V content is controlled at 0.10-0.20%.

[0050] Ti, B: When Ti and B are added together, B is concentrated at the grain boundary, reducing the grain boundary vacancy concentration and reducing hydrogen diffusion, thereby improving the SSC resistance. When the Ti content is too high, in addition to forming coarse carbides, it will also increase the bainite and M / A islands in the steel, thereby reducing the SSC resistance. Therefore, the Ti content is controlled at 0.030-0.050%, and the B content is controlled at 0.0010-0.0030%.

[0051] RE: Rare earth elements can transform strip-shaped MnS in steel into spherical sulfides, which can reduce the concentration of hydrogen atoms in strip-shaped MnS inclusions and reduce the sensitivity to hydrogen-induced cracking. Therefore, the RE content is controlled at 0.0010-0.0020%.

[0052] P, S and five harmful elements: P, S and five harmful elements Sn, Sb, As, Pb, Bi are impurity elements in steel, which significantly reduce the material's SSC resistance. Their content in steel should be reduced as much as possible. P is easy to form segregation in steel, and the stress zone at the tip of MnS inclusions is easy to become the starting point of sulfide stress cracking. Therefore, P, S and five harmful elements should be controlled at ≤0.010%, ≤0.0015% and ≤0.010% respectively.

[0053] TO and [N]: Oxygen in steel easily forms oxide inclusions, especially type B inclusions along the rolling direction. The presence of free nitrogen increases the brittleness of the material and impairs its toughness. The total amount of T.O + [N] should be ≤120ppm.

[0054] In order to ensure the good low-temperature toughness of steel, the ratio of Si, Mo, Mn, Ni, Ti, V and B needs to be limited. Since Si is easy to segregate at the austenite grain boundary, it reduces the crystal bonding force, deteriorates the low-temperature toughness and increases the temper brittleness, so the coefficient of Si is -2.0. Mn can significantly affect the variant selection during the phase transformation process, increase the types of variants in the phase transformation, and thus improve the low-temperature toughness, so the coefficient of Mn is 1.0; Mo can improve the hardenability of steel, effectively reduce the segregation of impurity elements such as P, S, and As at the grain boundary, and effectively improve the low-temperature toughness of steel, so the coefficient of Mo is 1.3; Ni significantly reduces the tough-brittle transition temperature of steel and improves the low-temperature toughness, so the coefficient of Ni is 2.5; V can precipitate fine MC carbides, refine the structure and improve the tempering stability of steel, thereby improving the low-temperature toughness, so the coefficient of V is 2.0; when Ti and B act together, the refinement effect is more significant. The carbonitride formed by Ti provides more nucleation sites for the segregation of B at the grain boundaries, allowing B to more effectively inhibit grain boundary migration. The two cooperate with each other to further improve the degree of grain refinement, thereby improving the low-temperature toughness of the material. Therefore, the coefficient of Ti and B is 5.0.

[0055] That is, α=-2.0×%Si+1.0×%Mn+1.3×%Mo+2.5×%Ni+2.0×%V+5.0×(%Ti+B%)≥2.90%.

[0056] In order to ensure the good hydrogen sulfide corrosion resistance of steel, the ratio of Si, Mn, Cr, Mo, V, Ti and B needs to be limited. Since Si and Mn are easy to segregate at the austenite grain boundary, the crystal bonding force is reduced, resulting in uneven microstructure and decreased corrosion resistance, so the coefficient is -5. Mo can improve the hardenability of steel, effectively reduce the segregation of impurity elements such as P and S at the grain boundary, and precipitate carbide Mo2C during tempering, which can become a trap for capturing H, effectively improving the sulfur resistance of steel, so the coefficient of Mo is 12; the MC-type carbide precipitated by V can effectively inhibit grain growth, and as an irreversible H trap, greatly improve the SSC resistance. In addition, it can improve the tempering softening resistance of steel, reduce the dislocation density of the material, and improve the SSC resistance, so the coefficient of V is 18; Ti carbide is an irreversible trap for hydrogen. When Ti and B are added in combination, B also toughens the grain boundary, and its solid solution amount increases due to Ti solidification of N. B is concentrated at the grain boundary, significantly improving hardenability, increasing martensite content, and effectively reducing the Mn content in the steel; on the other hand, B reduces the diffusion of hydrogen by reducing the vacancy concentration at the grain boundary. Therefore, the coefficient of Ti and B is 22. The irreversible hydrogen trap provided by Cr can effectively capture H atoms, slow down the diffusion rate of H atoms, and improve the anti-SSC performance, so the coefficient of Cr is 10.

[0057] That is, β=-5×(%Si+%Mn)+12×%Mo+10×%Cr+22×(%Ti+%B)+18×%V≥18.00%.

[0058] The inventors found that inclusions in steel (especially MnS inclusions) are the main cause of hydrogen-induced cracking and the starting point of HIC. The hydrogen-induced cracking caused by inclusions is first determined by its shape. Strip-shaped MnS is more harmful than elliptical MnS. Through reasonable refining treatment technology, the addition of rare earth elements and the control of the refining process, the control of MnS

[0059] The aspect ratio of the morphology is less than 3, and the two ends are relatively smooth. Reducing the content of type II MnS in steel and controlling its morphology can effectively improve the SSC resistance of steel.

[0060] The suitable component system and the two-time quenching and tempering heat treatment process of the present invention ensure the mechanical properties and hydrogen sulfide resistance of the material, and at the same time cooperate with the clean steel smelting technology to reduce the influence of non-metallic inclusions and component segregation in the steel on the material properties.

[0061] Compared with the prior art, the present invention adopts an optimized alloy component system, combined with appropriate steelmaking process and heat treatment process, and can obtain a dispersed and refined second phase distributed on the tempered troostite matrix at room temperature, with lower dislocation density and high-angle grain boundary ratio, while improving the morphology of type II MnS and reducing the concentration of H atoms, so that the material has good toughness and excellent resistance to hydrogen sulfide corrosion. It can be applied to the exploitation of 10,000-meter oil wells. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is the EBSD large and small grain boundary map of Example 1, where the large-angle grain boundaries account for 65%;

[0063] Figure 2 This is the EBSD large and small grain boundary map of Comparative Example 1, in which large-angle grain boundaries account for 78%. DETAILED DESCRIPTION

[0064] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] Example 1-Example 3

[0066] A high-grade SSC-resistant steel for oil well pipes comprises the following components in mass percentage: as shown in Table 1, the remainder not shown in Table 1 is Fe and unavoidable impurities.

[0067] Comparative Example 1-Comparative Example 3

[0068] A high-grade SSC-resistant steel for oil well pipes comprises the following components in mass percentage: as shown in Table 1, the remainder not shown in Table 1 is Fe and unavoidable impurities.

[0069] Table 1 Steel composition of each embodiment and comparative example (wt%)

[0070]

[0071] The examples and comparative examples in Table 1 use the same rare earth raw materials, but control the RE content differently. In addition, the five harmful elements Sn, Sb, As, Pb, and Bi are controlled at ≤0.010%.

[0072] The production method of the high-grade SSC-resistant oil well pipe steel described in each embodiment and comparative example includes the following process flow: electric arc furnace smelting→LF furnace refining→RH vacuum degassing→round billet continuous casting.

[0073] The electric arc furnace smelting: steel is deoxidized and alloyed, and the amount of slag is strictly controlled.

[0074] The LF furnace refining: elements such as C, Si, Mn, Cr, Ni, Mo, V, Ti, and B are adjusted to target values, the white slag retention time is ≥20 minutes, and the smelting cycle is ≤80 minutes.

[0075] The RH vacuum degassing: pure degassing time ≥ 25min, soft blowing time ≥ 20min, [H] ≤ 1.0ppm after vacuum treatment, adding any one or more of rare earth elements La or Ce to make the rare earth content 0.0010-0.0020%.

[0077] The continuous casting: adopts an immersion nozzle and protective slag casting to prevent secondary oxidation and absorb the floating inclusions in the molten steel, producing a continuous casting round billet with a diameter of 450mm, a superheat of 47°C, a casting speed of 0.41m / min, and meets v=1.83×(D / 1000) 2 -3.04×(D / 1000)+1.41; the crystallizer electromagnetic stirring frequency is 2.25Hz, and the end electromagnetic stirring frequency is 4.5Hz, which satisfies D / f1=200 and does not satisfy D / f2=100.

[0078] In the actual production of the steel in the above embodiments and comparative examples, the production can be achieved by controlling within the above process range.

[0079] The oil well pipes produced by using the high-grade SSC-resistant oil well pipe steels of the above embodiments and comparative examples have a pipe manufacturing route as follows: the above-produced ingot → hot-rolled round steel → heating → pipe threading → sizing → heat treatment → steel pipe grinding → steel pipe flaw detection → fine machining → flaw detection → packaging and warehousing.

[0080] The heat treatment includes two quenching and two tempering. Specifically, first quenching is performed, then tempering is performed, then secondary quenching is performed, and finally secondary tempering is performed.

[0081] The primary quenching: heating temperature W1 = AC3 + 30 ~ 50 ° C, holding time t1 is determined by the steel pipe wall thickness S, t = 3.5 × S, water cooling. Among them, the unit of heating temperature W1 is ° C, the unit of holding time t1 is min, and the unit of steel pipe wall thickness S is mm. AC3 is tested using Gleeble-2000D thermal simulation test machine equipment. W1 of each embodiment and comparative example satisfies W1 = AC3 + 30 ~ 50 ° C.

[0082] Primary tempering: tempering temperature 700-730℃, holding time t2 is determined by the steel pipe wall thickness S, t2=6×S, air cooling. The unit of holding time t2 is min, and the unit of steel pipe wall thickness S is mm.

[0083] Secondary quenching: heating temperature W2 = W1-20°C, holding time t3 is determined by the steel pipe wall thickness S, t3 = 3.5 × S, water cooling. Among them, the unit of heating temperature W2 is ℃, the unit of holding time t3 is min, and the unit of steel pipe wall thickness S is mm.

[0084] Secondary tempering: tempering temperature 680 ~ 710 ℃, holding time t4 is determined by the steel pipe wall thickness S, t4 = 6 × S, air cooling. Among them, the unit of holding time t4 is min, and the unit of steel pipe wall thickness S is mm.

[0085] The heat treatment processes of various embodiments and comparative examples are shown in Table 2.

[0086] Table 2 List of heat treatment processes for the embodiments of the present invention and comparative examples

[0087]

[0088] The performance testing methods of the oil well pipes produced in each embodiment and comparative example are as follows:

[0089] Organization: Take samples from 1 / 2 wall thickness of the cross section at the end of the steel pipe for metallographic and grain size analysis.

[0090] Performance: Tensile, impact and SSC resistance specimens were taken on the 1 / 2 radius of the steel pipe, and mechanical properties tests were carried out in accordance with GB / T228 and GB / T229. EBSD was used to observe and analyze high-angle grain boundaries (15°≤θ≤62.5°). The SSC resistance test was carried out in accordance with NACE TM0177 standard A method (at a loading strength of 75% SMYS, a H2S partial pressure of 0.1MPa, and a temperature of 25°C), and the average grain size was observed in accordance with GB / T6394. The results are shown in Table 3.

[0091] Non-metallic inclusions are sampled from the 1 / 2 radius of the steel pipe and tested according to method A in ASTM E45 standard. The properties are shown in Table 4.

[0092] Table 3 Performance test results of the embodiments of the present invention and the comparative examples

[0093]

[0094]

[0095] Table 4 Non-metallic inclusion detection results of the embodiments of the present invention and the comparative examples

[0096]

[0097] The chemical composition and production methods of the steel in Examples 1, 2 and 3 are properly controlled, and their chemical compositions meet the requirements, and the strength, toughness and SSC resistance of the steel are good. The chemical composition of Comparative Example 1 is appropriate, but the β value does not meet the requirements. Even if it is produced according to the heat treatment process of the present invention, the product grains are large and the proportion of high-angle grain boundaries is high. From the perspective of the material substructure, the proportion of high-angle grain boundaries in the material exceeds 70%, which will affect the material's sulfur resistance. Therefore, the SSC resistance of Comparative Example 1 is extremely poor. The chemical composition of Comparative Example 2 is appropriate, but only the α value does not meet the requirements. Even if it is produced according to the heat treatment process of the present invention, the product grains are large, and the strength and low-temperature toughness are reduced. The chemical composition of Comparative Example 3 is properly controlled, but the heat treatment process is improper, resulting in unsatisfactory overall performance.

[0098] The underlined data above do not meet the requirements of the present invention.

[0099] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A high-grade SSC-resistant steel for oil well pipes, characterized in that: The high-grade SSC-resistant oil well pipe steel comprises the following components in percentage by mass: Cr: 0.95~1.20%, Ni: 0.40~0.60%, Mo: 0.75~0.95%, Ti: 0.030~0.050%, B: 0.0010~0.0030%, Al: 0.020~0.045%, V: 0.10~0.20%, RE: 0.0010~0.0020%, C: 0.25~0.30%, Si: 0.15~0.30%, Mn: 0.60~0.75%, P≤0.010%, S≤0.0015%, and the rest are Fe and other inevitable impurities.

2. The high-grade SSC-resistant steel for oil well pipe according to claim 1, characterized in that: The composition of the high-grade SSC-resistant oil well pipe steel also satisfies: α = -2.0×%Si+1.0×%Mn+1.3×%Mo+2.5 ×%Ni+2.0×%V+5.0%×(Ti+B)≥2.90%.

3. The high-grade SSC-resistant steel for oil well pipe according to claim 1 or 2, characterized in that: The composition of the high-grade SSC-resistant oil well pipe steel also satisfies: β = -5×(%Si+%Mn)+12×%Mo+10 ×%Cr+22×(%Ti+%B)+18×%V≥18.00%.

4. A method for producing high-grade SSC-resistant oil well pipe steel according to any one of claims 1 to 3, characterized in that: The production method comprises the following process flow: electric arc furnace smelting→LF furnace refining→RH vacuum degassing→round billet continuous casting.

5. The production method according to claim 4, characterized in that: The continuous casting: continuous casting round billet: the diameter of the continuous casting round billet D, and the drawing speed v should meet v = 1.83 × (D / 1000) 2 -3.04×(D / 1000)+1.41, where the unit of the continuous casting billet diameter D is mm, and the pulling speed is m / min; the crystallizer electromagnetic stirring frequency f1 and the continuous casting billet diameter D should comply with D / f1=200; the terminal electromagnetic stirring frequency f2 and the continuous casting billet diameter D should comply with D / f2=100, where the unit of the crystallizer electromagnetic stirring frequency f1 is Hz, the terminal electromagnetic stirring frequency f2 is Hz, and the unit of the continuous casting billet diameter D is mm.

6. A heat treatment process for oil well pipes, characterized in that: The oil well pipe produced by using the high-grade SSC-resistant oil well pipe steel according to any one of claims 1 to 3 is subjected to heat treatment, wherein the heat treatment comprises: first quenching, then tempering; then secondary quenching, and finally secondary tempering.

7. The heat treatment process according to claim 6, characterized in that: The primary quenching: heating temperature W1=AC3+30~50℃, holding time t1 is determined by the steel pipe wall thickness S, t=3.5×S, water cooling; wherein, the unit of heating temperature W1 is ℃, the unit of holding time t1 is min, and the unit of steel pipe wall thickness S is mm.

8. The heat treatment process according to claim 6, characterized in that: The primary tempering: the tempering temperature is 700-730°C, the holding time t2 is determined by the steel pipe wall thickness S, t2=6×S, and air cooling; wherein the unit of the holding time t2 is min, and the unit of the steel pipe wall thickness S is mm.

9. The heat treatment process according to claim 6, characterized in that: The secondary quenching: heating temperature W2 = W1-20°C, holding time t3 is determined by the steel pipe wall thickness S, t = 3.5×S, water cooling; wherein, the unit of heating temperature W2 is °C, the unit of holding time t3 is min, and the unit of steel pipe wall thickness S is mm.

10. The heat treatment process according to claim 6, characterized in that: The secondary tempering: the tempering temperature is 680-710°C, the holding time t4 is determined by the steel pipe wall thickness S, t4=6×S, and air cooling; wherein the unit of the holding time t4 is min, and the unit of the steel pipe wall thickness S is mm.

11. An oil well pipe, characterized in that: The oil well pipe is produced by the heat treatment process according to any one of claims 6 to 10, wherein the grain size at the half wall thickness of the cross section of the oil well pipe is ≥8.5; the high-angle grain boundary ratio of the oil well pipe is ≤70%, and the dislocation density is 7.0×10 13 / m 2 ~9.0×10 13 / m 2 The total amount of Class A, Class B, Class C, Class D and Class DS inclusions of the oil well pipe is less than Level 4.0, and the Class A, Class B, Class C, Class D and Class DS inclusions do not exceed Level 1.

0.

12. The oil well pipe according to claim 11, characterized in that: The room temperature mechanical properties of the oil well pipe are yield strength ≥950MPa, and impact energy ≥100J at -20°C. The oil well pipe passes the hydrogen sulfide corrosion test using the American standard NACE TM0177 standard A method at a loading strength of 75% SMYS, a H2S partial pressure of 0.1MPa, and a temperature of 25°C, and no fracture occurs during the test for 720 hours.

13. Use of the oil well pipe according to claim 11 or 12, characterized in that: Used for exploitation of 10,000-meter oil wells.

Citation Information

Patent Citations

  • High strength seamless steel pipe with excellent low temperature toughness and manufacturing method thereof

    CN103160752A

  • 125ksi steel-grade sulfur-resistance oil well pipe and making method thereof

    CN110616366A

  • Petroleum casing pipe with high strength and high toughness and preparing method thereof

    CN101586450A

  • 95Ksi steel-grade hydrogen sulfide stress corrosion resistance low-alloy steel for oil well pipe

    CN106119708A

  • High strength seamless steel pipe for use in oil wells and manufacturing method thereof

    CN106687613A